A new species of Opisthosyllis (Polychaeta: Syllidae) from California (U.S.A.) - Aguado, M. Teresa; San Martín, Guillermo; Nygren, Arne (Zootaxa, 2005)
Opisthosyllis leslieharrisae n. sp. is described from Santa Catalina Island, California. It differs from all other species of the genus in the following characters: dorsum densely covered by papillae in two sizes, and a distinct colour pattern consisting of white spots distributed transversally along the segments (only seen in live specimens) and dark red areas located on cirrophores, over the third segment, and in the middle of the second and the remainder segments (maintained in formalin fixed specimens). The new species is also characterized by the tooth located in the third quarter of the pharynx, and long spines on the blades of compound chaetae.